ANALISIS TITIK PULANG POKOK USAHA ABON SAPI PADA INDUSTRI RUMAH TANGGA MUTIARA HJ MBOK SRI DI KOTA PALU - Pareira, Frederikus Egidius; Antara, Made; Alam, Max Nur (AGROTEKBIS, 2013)
Beef Abon is made from shredded beef mixed with spices and favorite to all ages, this Abon is very familiar among Indonesian that bring apparently business opportunity to people. This study aimed to study the cost, the amount of production, selling prices and revenues received during this Abon business reached its break-even point. Results showed that beef Abon products sell in a 500 g packaged reaches the break-even point at 33 packs, selling price shall be 137, 500 IDR per pack with revenue of 4,537, 500 IDR; and a 400 g package reaches its break-even point at 30 packs, the selling price is 110,000 IDR with revenue of 3,300,000 IDR, for a 250 g package the break-even point reaches 32 packs, selling price is 68, 750 IDR per pack and revenue is 2,232,000 IDR, for a 200 g package the break-even point is 31 packs , the selling price will be 55,000 IDR with revenue of 1,705,000 IDR, and a 100 g package has break-even point at 31 packs and selling price of 27,500 IDR per pack with revenues of 852,500 IDR.